Penilaian dan Mitigasi Risiko Keamanan di PT. Unilever Indonesia Tbk: Pendekatan Komprehensif untuk Melindungi Aset, Keuangan, dan Kekayaan Intelektual - Edy Susanto; Damar Asmarani; Donni Ferdinan Irawan; Putri Octavia Maharani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Generally, the purpose of a company is to maximize its value. This goal is absolute for every company regardless of its business type. Therefore, companies can be demanded to perform their operational activities effectively and efficiently, so that those who can manage their assets more effectively and efficiently will also benefit. As the company grows, it can develop to follow and meet the ever-changing market needs and compete to obtain the best management capability. Financial conditions and healthy company developments will reflect efficiency in performance, becoming the main demand to compete with other companies. The method used in this research is qualitative research and literature study. Based on the research that has been conducted, the results are that employees and central departments of PT. Unilever Indonesia Tbk must apply things such as reporting to the Legal Group on any suspected fake or infringing Unilever products, packaging, communication practices or marketing that violate copyrights, trademarks, patents, designs, domain names, and/or intellectual property rights, ensuring all required inspections and submissions related to patents, designs, trademarks, or other intellectual property rights have been completed, when researching, developing, or applying the launch of new brands, sub-brands, services, designs, inventions, communications, advertising, and promotional materials, ensuring contract enforcement with clauses suitable for protecting Unilever's intellectual property rights.